Combining ability for grain yield and yield components in local inbred lines and introduced open pollinated varieties of maize (Zea mays L) - Alhussein, Mohammedein B.; Ibrahim, Abu Elhassan S.; Ali, Eltahir S. (Gezira Journal of Agricultural Science; Vol 11 No 1 (2013), 2013)
ABSTRACT  The development of hybrids is the main objective of maize breeding. However, success depends largely on the identification of the best parents to ensure maximum combining ability. This study was conducted to estimate genetic variability and combining ability for grain yield and yield components of seven local inbred lines and four introduced open pollinated varieties of maize ( Zea mays L.) across two irrigated locations, Medani and Matuq, Gezira, Sudan in 2008. The experiment was arranged in a randomized complete block design with three replicates. The traits measured were days to 50% tassel, plant height, ear length, ear diameter, hundred kernels weight and grain yield. Significant differences were observed among the parents and crosses for most of studied traits in both seasons. The crosses showed high genetic variability and tall plants than their parents which suggested some degree of hybrid vigor. The tallest hybrids across locations were T3 x L5 and T4 x L3. This indicates that the crosses were late maturing than their parents. The highest yielding hybrids had long ears and better shape, e.g., T2 x L1 and T1 x L7.The top five ranking crosses for grain yield across locations were T2 x L7 (3.45 t/ha), T1 x L2 (3.44 t/ha), T2 x LI (3.32 t/ha), T4 x L4 (3.30 t/ha) and T1 x L1 (3.13 t/ha).   The inheritance of most traits was controlled by non-additive gene action except ear height and grain yield. The best combiners for grain in Medani were T4, L4 and L5, while in Mutaq were L2, L4 and L6. The ratio of GCA to SCA variance for the most traits was less than one, suggesting that the inheritance was due to non additive gene effect with the exception of grain yield being more than one, indicating that inheritance of this trait was due to GCA effects, and was largely controlled by additive gene action in the base material. From these results it is recommended that parents T4, L1 and L6 to be used in recurrent selection, while, crosses T3 x L5, T1 x L5 and T4 x L6 to be tested in multi-locations trials for commercial utilization.